Cerebral Amyloid Angiopathy in the Elderly - Viswanathan, Anand (2011)
Cerebral amyloid angiopathy (CAA) results from deposition of β-amyloid in the media and adventitia of small arteries and capillaries of the leptomeninges and cerebral cortex and is a major cause of lobar intracerebral hemorrhage and cognitive impairment in the elderly. CAA is associated with a high prevalence of magnetic resonance imaging markers of small vessel disease, including cerebral microbleeds and white matter hyperintensities. Although advanced CAA is present in approximately ¼ of brains with Alzheimer disease (AD), fewer than half of CAA cases meet pathologic criteria for AD. This review will discuss the pathophysiology of CAA and focus on new imaging modalities and laboratory biomarkers that may aid in the clinical diagnosis of individuals with the disease.